2005
DOI: 10.1128/aem.71.4.2016-2025.2005
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Oxygenase Genes from Methane- and Ammonia-Oxidizing Bacteria in the Eastern Snake River Plain Aquifer

Abstract: PCR amplification, restriction fragment length polymorphism, and phylogenetic analysis of oxygenase genes were used for the characterization of in situ methane-and ammonia-oxidizing bacteria from free-living and attached communities in the Eastern Snake River Plain aquifer. The following three methane monooxygenase (MMO) PCR primer sets were used: A189-A682, which amplifies an internal region of both the pmoA gene of the MMO particulate form and the amoA gene of ammonia monooxygenase; A189-mb661, which specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 47 publications
4
38
0
Order By: Relevance
“…The clone library RFLP analysis revealed one major OTU (88% of clone library) with closest sequence similarity to a known Methylobacter pmoA gene sequence (AAF08210) (Costello and Lidstrom, 1999). The two remaining low-abundance OTUs, both with a relative abundance of 6%, were similar to pmoA clones from uncultivated bacteria collected from a river plain aquifer (AAZ06139) (Erwin et al, 2005) and a sand water filter (ABC59829) (Stoecker et al, 2006).…”
Section: Resultsmentioning
confidence: 83%
“…The clone library RFLP analysis revealed one major OTU (88% of clone library) with closest sequence similarity to a known Methylobacter pmoA gene sequence (AAF08210) (Costello and Lidstrom, 1999). The two remaining low-abundance OTUs, both with a relative abundance of 6%, were similar to pmoA clones from uncultivated bacteria collected from a river plain aquifer (AAZ06139) (Erwin et al, 2005) and a sand water filter (ABC59829) (Stoecker et al, 2006).…”
Section: Resultsmentioning
confidence: 83%
“…3) (32). Clone a3 (30% of total clones) was closely related to pmoA genes of the recently described yet uncultivated filamentous methanotroph Crenothrix polyspora (39) and to a large group of sequences recovered from the Eastern Snake River Plain aquifer, designated group II unculturables (16). While C. polyspora is a gammaproteobacterium, its pmoA sequence has been noted to be more closely related to amoA sequences and to the divergent alphaproteobacterial sequences (cluster 1) (39) than to gammaproteobacterial sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of methanotroph abundance in natural samples are based on a number of complementary techniques, such as determination of methane oxidation rates (3,9,29,40), determination of the fatty acid composition of the total microbial population (9,29,40), PCR-based (2,14,15,19,25,26,28), quantitative PCR-based (5,27,29), or reverse transcriptase PCR (RT-PCR)-based (24,32) surveys, and direct counting using microscopy combined with fluorescence in situ hybridization (FISH) (6,8,10). The most widely used PCR primers for detecting type I and type II methanotrophic bacteria target rRNA genes (15,19) or functional genes encoding particulate methane monooxygenase (pmoA) (14), methanol dehydrogenase (mxaF) (14), formaldehyde-activating enzyme (fae) (25), or the D subunit of the formyltransferase/hydrolase complex (fhcD) (25), and large databases of these genes have been compiled from a variety of environments (5,11,14,16,19,24,26,28,31,33,39,40). The most widely used FISH probes target rRNA (15,19); however, several protocols have be...…”
mentioning
confidence: 99%
“…The ESRPA is a deep basalt aquifer and is considered oligotrophic (4,22,29); however, previous work has demonstrated the presence of ureolytic microbes in this environment (11,13). Erwin et al also reported evidence of AOB during the analysis of methane monooxygenase clone libraries from ESRPA samples (7), but in general, the structure and function of ammonia-oxidizing microbial communities (and especially AOA) in deep aquifers like the ESRPA have been relatively unexplored.…”
mentioning
confidence: 99%